Legal Protection Against The Fulfilment of Children's Rights Due to Parental Divorce - Monike Khasanah (UM Purwokerto Press, 2023)
Marriage is the beginning of the formation of a family, where the family becomes the main place filled with love and affection, and the fulfilment of the rights of a child is guaranteed. However, in marriage it does not go well, there are times when various problems arise which eventually get a resolution point but not a few also end in divorce. The party who is harmed by this divorce is the child, because of this condition the child loses his rights that he should get from his parents. Therefore, protection is needed so that children's rights can be fulfilled. The issues raised in this paper are how the practice of fulfilling children's rights after parental divorce. The purpose of this writing is to find out the practice of fulfilling children's rights by parents after divorce. The research method of this writing uses empirical juridical research. With interview collection tools and literature study. The results of the study show that in fact the regulations made by the state are sufficient to provide protection to children after parental divorce. So, even though it has been clearly enacted, the implementation of legal protection for children after divorce has not been implemented properly so that there are still a lot of children who do not get their full rights after a divorce between the parents. And this results in many new problems in children's lives that impact their growth and development both physically and psychologically.